Traumatic childhood experience and self-harm behaviour in adolescent: a review - Mat Zin, Nora; Irwandi, Uzma Nadhirah (Padang: INSIGHT - Indonesian Society for Knowledge and Human Development, 2022)
The rate of self-harm in adolescents is increasing and therefore has become a wide-spread public health problem. According to a metaanalytic study done in 2018, the lifetime prevalence of self-harm is 16.9% with the average age of starting self-harm was 13 years, and adolescents who self-harm also have a significantly higher risk of suicidal ideations and attempts. This paper reviews studies related to traumatic childhood experience and its relations to self-harm behaviour in adolescent. Several topics are discussed in more details, i.e. traumatic childhood and selfharm behaviour in adolescent themselves, roles of traumatic childhood experience in the development of suicidality, understanding the psychopathology of self-harm and traumatic childhood experiences, emotion dysregulation as a mechanism, possible mediators, preventing self-harm behaviour in adolescent with traumatic childhood experience, and the Islamic inputs on the topic discussed. This information may help to early detect and rapidly recognize those who experienced childhood trauma as a specific group at risk for NSSI and suicidal behaviours. Therefore, we recommend that higher risk group such as adolescents that has a history of any form of childhood trauma should be given the necessary intervention before possibly engaging in any self-harm behaviour. Future research should explore systematically the role of vulnerability and protective factors, i.e., factors that may act to increase or attenuate, respectively, the association between childhood trauma and NSSI.